The Dynamics of Legal Protection in Indonesia Against the Role of the Second Wife - Suharti, Suharti; Putri, Suci Ramadhani; Nizamudin, Nizamudin; Mulhimmah, Baiq Ratna (Alhurriyah, 2025)
This article aims to comprehensively examine polygamy from various perspectives, with a particular focus on the legal protection afforded to second wives within polygamous practices in Indonesia. It explores the complex dynamics experienced by women who occupy the position of a second wife, including their roles, rights, and social perceptions. Furthermore, this study seeks to deconstruct the existence and identity of women in polygamous marriages by critically assessing the challenges they face and the efforts made to safeguard their legal and social well-being. Employing a qualitative research approach, this study utilizes Simone de Beauvoir’s existentialist feminism theory as an analytical framework to understand how women’s roles in polygamy are constructed and contested within patriarchal legal and social systems. The findings reveal that, although polygamy is permitted under Indonesian law, its practical implementation often leads to various injustices, particularly in the form of legal uncertainty and limited protection for second wives. These women frequently encounter stereotyping, social stigma, discrimination, and even the threat of criminal consequences when the polygamous marriage is carried out without the consent of the first wife. This article advocates for the reconstruction of the identity and social role of second wives, emphasizing the need for comprehensive legal reforms, increased public awareness, and the promotion of marriage registration to ensure the fulfillment of women’s rights and the creation of a more equitable marital framework in polygamous settings.